A semantic web based framework for preschool cognitive skills tutoring system - Abbas, M.A. (Asian Research Publishing Network, 2015)
Intelligent tutoring system (ITS) is a contribution of the artificial intelligence domain, which supports the pedagogical activities. The development of a constructive intelligent tutoring system following psychology, intelligence, interactivity, creativity and personalization for any real domain is highly complex. To address this complexity, a semantic web based framework, called MySekolah was presented in this paper. The proposed framework comprise of integrated set of models using ontologies i.e. domain model, student model, assessment and expert models. The goal of the proposed framework is to provide an overall structure for the construction of an intelligent tutoring system. More specifically, to model the domain knowledge and generate learning contents through the use of expert based reasoning technique. As a sample, modeling of the preschool cognitive skills is demonstrated. A prototype application is developed to validate the framework. Finally, evaluation shows the correctness of the cognitive skills learning content generated from the modeled ontology.